Peningkatan Penjualan CV. Keripik Balado Mahkota dengan Merancang Sistem Informasi Pemasaran dan Penjualan Berbasis E-Commerce - Nilda Tri Putri (Jurnal Pengabdian Warta Andalas, 2016)
Information system is a combination of information technology and the activities of people using the technology to support the operation. A good information system can be seen through the effectiveness of information systems and to improve the performance of all elements of the organization are supported by accurate data and more secure, so that all activities can be run more effectively. CV. Mahkota is one company that is engaged in the food industry. One part of the company that plays an important part of marketing and sales. It is important in the marketing and sales is how to introduce and demonstrate products and transactions that can be done all over the world. In this section we still use the traditional system of face-to-face transactions. Therefore, the need to design a computerized information system so that sales are expanding the sales area and facilitate the transaction. This information system design through several stages beginning with the survey company, problem identification, system analysis, design models using UML and finally by designing systems using database information and applications with PHP-MySQL.